Greater Intake of Fruit and Vegetables Is Associated with Greater Bone Mineral Density and Lower Osteoporosis Risk in Middle-Aged and Elderly Adults - Qiu, Rui; Cao, Wen-ting; Tian, Hui-yuan; He, Juan; Chen, Geng-dong; Chen, Yu-ming (PLOS ONE, 2017)
Objective A few studies have suggested that the consumption of fruit and vegetables (FV) may benefit bone health, but limited data are available in Asian subjects. We examined the association between FV intake and bone mineral density (BMD) and osteoporosis in Chinese adults. Methods This population-based cross-sectional study involved 2083 women and 1006 men aged 40–75 years in Guangzhou, China. Habitual dietary data was collected from a 79-item food frequency questionnaire by face-to-face interviews. The BMD was measured for the whole body (WB), lumbar spine (LS), total hip (TH) and femur neck (FN) with dual-energy X-ray absorptiometry. Results After adjustment for potential covariates, we observed dose-dependent associations between total FV intake and BMD and osteoporosis risk. The mean BMD was higher in tertile 3 vs. tertile 1 by 1.33% (TH) and 1.31% (FN) for FV, and 1.10% (WB), 1.57% (TH), and 2.05% (FN) for fruit (all P-trends < 0.05). Significant beneficial associations with BMD at some sites were also found in most fruit categories but not in total vegetables or their subgroups. The odds ratios (95% confidence interval) of osteoporosis (T-score ≤ −2.5) in tertile 3 (vs. 1) were 0.73 (0.58–0.92), 0.37 (0.22–0.60), and 0.71 (0.52–0.97) for FV; 0.82 (0.66–1.03), 0.48 (0.30–0.77) and 0.89 (0.61–1.12) for fruit; and 0.80 (0.64–1.01), 0.57 (0.35–0.92) and 0.76 (0.55–1.05) for vegetables at the LS, TH, and FN, respectively. The favorable association between FV intake and the occurrence of osteoporosis was evident only in subjects with lower BMI (<24.0 kg/m2, P-trends < 0.05). Conclusions Greater intake of FV was independently associated with a higher BMD and a lower presence of osteoporosis in middle-aged and elderly Chinese subjects with lower BMI. Fruit tended to have more contribution to the favorable association than vegetables.